2020
DOI: 10.1111/jvh.13252
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the hepatitis B care cascade in Australia: A cost‐effectiveness model

Abstract: If Australia is to successfully eliminate hepatitis B as a public health threat, it will need to enhance the chronic hepatitis B (CHB) care cascade. This study used a Markov model to assess the impact, cost and cost‐effectiveness of scaling up CHB diagnosis, linkage to care and treatment to reach national and international elimination targets for hepatitis B in Australia. Compared to continued current trends, the model calculated the difference in care cascade projection, disability‐adjusted life years (DALYs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 34 publications
(26 reference statements)
0
16
0
Order By: Relevance
“…A 2009 study found that appropriate treatment was not only cost‐effective but more so than many currently existing population‐based cancer prevention programs 14 . More recent research has also suggested that improving the hepatitis B cascade of care in Australia is cost‐effective 15 …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A 2009 study found that appropriate treatment was not only cost‐effective but more so than many currently existing population‐based cancer prevention programs 14 . More recent research has also suggested that improving the hepatitis B cascade of care in Australia is cost‐effective 15 …”
mentioning
confidence: 99%
“… 14 More recent research has also suggested that improving the hepatitis B cascade of care in Australia is cost‐effective. 15 …”
mentioning
confidence: 99%
“…Multiple studies have demonstrated cost-effectiveness of HBV screening in a variety of different scenarios, including community-based outreach and low prevalence settings ( Su et al, 2022 , Xiao et al, 2020 , Toy et al, 2022 , Nayagam et al, 2016 , Tordrup et al, 2020 , Hutton et al, 2022 , Wright et al, 2018 ). This is largely due to averting high costs associated with decompensated cirrhosis, HCC and liver transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…In Australia, the epidemiology of HBV is complex, with a high prevalence among migrants from high-or J o u r n a l P r e -p r o o f intermediate HBV prevalence countries and Aboriginal or Torres Strait Islander peoples (15,16). Over the past two decades, remarkable strides have been made in increasing HBV diagnosis, vaccination and treatment uptake (17) and understanding the epidemiology, risk factors, and molecular profiles of HBV-related DC and HCC (18). However, enhanced HBV diagnosis and treatment uptake are needed if Australia is to achieve the WHO 2030 elimination targets (6).…”
Section: Introductionmentioning
confidence: 99%